دور طريقة برايل يف دمج املكفوفني ومتكينهم يف اجملتمع - Muhammad ‘Ashour Abdullah Kushlaf,; Ahmad Yunus Mohd Noor, (Penerbit Universiti Kebangsaan Malaysia, 2024)
People with special needs with regards to any person who has a disability in one of his senses or organs of his body are part of the human being for states. This requires taking care of them and providing them with all capabilities so that other individuals can participate in building and advancing their society, and thus, become a participant in the renaissance and development of society. Caring for the blind has become a human right and a societal duty. Therefore, education must be made available to the blind. It has become necessary for society to provide the blind with the opportunity to learn Braille as it is the ideal method of education. Teaching Braille to the blind in different countries of the world in different languages will enable them to be integrated, empowered, and treated as ordinary people capable of performing their roles and serving their communities. In addition, Braille helps them acquire the technologies available in today’s world that increase empowerment and social integration. This article aims to focus on the important role that Braille plays in educating blind people, helping them get out of their isolation, enabling them to express themselves, and their ability to adapt and integrate into various social activities and contribute to building their society. The article also reviews some of the technologies that support the Braille method and help blind people quickly adapt and integrate socially. It also aims to reveal the challenges that stand in the Braille method. This research uses a qualitative research method with a text content analysis design. The findings of the study sum up the important role of braille in integrating blind people with learning disabilities. It is very significant through a series of works that can empower them in society.